2018
DOI: 10.2174/1567201815666180116090258
|View full text |Cite
|
Sign up to set email alerts
|

Taxifolin: Evaluation Through Ex vivo Permeations on Human Skin and Porcine Vaginal Mucosa

Abstract: The results suggest that, in the matrixes studied, TAX may be able to exert its biological activities systemically when applied by these routes. Furthermore, it exhibits greater permeability potential when administered by intravaginal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…They found that the bioavailability of oral taxifolin was 24% compared to intravenous injection. Studies on the bioavailability of drugs in humans are limited, with in vitro studies using human skin samples showing a bioavailability of 45 percent ( Alves et al, 2018 ). These may be reasons for neglect or failure in further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the bioavailability of oral taxifolin was 24% compared to intravenous injection. Studies on the bioavailability of drugs in humans are limited, with in vitro studies using human skin samples showing a bioavailability of 45 percent ( Alves et al, 2018 ). These may be reasons for neglect or failure in further clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The DHQ plasma concentration that could be required to saturate tissues for COVID-19 cannot be continuously maintained without increasing these daily doses because it has a short elimination half-life. The pharmacokinetics of DHQ differ for different substances and their modifications [14,15] and depend considerably on the administration mode [16] and excipients [17]. The properties of the dosage form, which determine the bioavailability, absorption time, elimination half-life, etc., which can significantly differ, must be considered in prescribing doses because DHQ is marketed in various forms and in combinations with other compounds.…”
Section: Possible Doses Pharmacokinetics and Safetymentioning
confidence: 99%
“…Experiments using porcine biomaterial showed that up to 87% of DHQ could penetrate the mucous membrane after intervaginal administration of an oil-in-water emulsion while penetration of human skin in the same emulsion reached up to 48% [16]. The bioavailability of a perorally administered DHQ lipid solution increased to 36% [17].…”
Section: The Bioavailability Problemmentioning
confidence: 99%
“…Ряд исследований показывают, что ДГК ингибирует процессы апоптоза, вызванные избыточным железом в печени у крыс [37]. ДГК проявляет схожую биодоступность у людей и крыс [38,39], а содержание железа в печени у крыс в эксперименте было сопоставимо с таковым для людей при перегрузке железом. Избыток железа приводит к значительному повышению перекисного окисления липидов и белков, а также снижению общей антиоксидантной способности тканей печени Нарушение функции печени, связанное с накоплением в ней железа в результате деградации гемоглобина, сопровождается выделением в кровь специфичного фермента аланинаминотрансферазы, который выступает маркером развития тяжелых форм COVID-19.…”
Section: точки приложения дигидрокверцетина при Covid-19unclassified